2016
DOI: 10.1007/s40620-016-0325-2
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle impairment in dialysis patients: can minimal dose of exercise limit the damage? A Preliminary study in a sample of patients enrolled in the EXCITE trial

Abstract: In dialysis patients, a minimal dose of structured exercise improved physical capacity and maintained a stable respiratory muscle function, in contrast to the control group where it worsened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…The positive effects of intradialytic exercise on VO 2peak were verified through the pulmonary ventilation values obtained during the maximum cardiopulmonary stress test. These results demonstrated the reduced ventilatory work of hemodialysis patients who exercised 25 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The positive effects of intradialytic exercise on VO 2peak were verified through the pulmonary ventilation values obtained during the maximum cardiopulmonary stress test. These results demonstrated the reduced ventilatory work of hemodialysis patients who exercised 25 .…”
Section: Discussionmentioning
confidence: 62%
“…Intradialytic exercise protocols are prescribed to improve the physical fitness of hemodialysis patients. Increased pulmonary ventilation is associated with cardiac performance, which influences the strength of the muscles involved in this mechanism, improving the respiratory system’s efficiency and, consequently, contributing to improved cardiopulmonary fitness 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The self-reported physical activity level was low among those of our individuals with lung dysfunction. One may speculate that physical exercise to improve muscle strength could have a beneficial impact on the muscles of respiration [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise has been shown to reduce the decline in pulmonary function in CKD [21,59]; in particular, studies designed specifically to strengthen the respiratory muscles have reported improved respiratory muscle strength and pulmonary function [59,[62][63][64]. Pomidori et al [65] reported improvements in respiratory muscle strength after a 6-month home walking program in MHD subjects, but no changes in FVC or FEV 1 . We observed a 28% improvement in FVC in the exercise group, a change with borderline significance (p = 0.07 between groups), and a change in FEV 1 (20%) that was larger than several previous studies with larger numbers in which these differences were significant [59,63].…”
Section: Discussionmentioning
confidence: 99%